On singularities of capillary surfaces in the absence of gravity. (1983) - Roytburd, V.
Abstract : We study numerical solutions to the equation of capillary surfaces in trapezoidal domains in the absence of gravity when the boundary contact angle declines from90 ° to some critical value. We also discuss a result on the behavior of solutions in more general domains that confirms numerical calculations.